A Synthesis and structural characterizations of tris(hydroxymethyl)amino-methanecomplexes with groupIIA metals - Lamia Albedair (Kuwait Journal of Science)
An investigation has been made into the tendency of tris(hydroxymethyl) aminomethane (THAM) to form stable complexes with group IIA metals. Four new complexes of group IIA metals [Ba(II), Ca(II), Sr(II) and Mg(II)] with THAM were prepared and obtained as colorless solid products. The reactions were conducted by stoichiometry of 2:1 (Ligand: Metal ion) at 65 °C and pH of ~ 8.5. Under these conditions, the THAM molecule (C4H11NO3) was deprotonated and transferred to the (C4H10NO3-; L-) chelate with the metal ions forming colorless products. The structures of these complexes were determined by UV-visible, IR, Raman and 1H NMR spectroscopies and other physicochemical and analytical methods (elemental analysis, thermogravimetry, and SEM). The outcome shows that the general composition of the complexes obtained with Ba(II), Ca(II), Sr(II) and Mg(II) ions are [BaL2(H2O)2], [CaL2(H2O)2]·2H2O, [SrL2(H2O)2], and [MgL2(H2O)2]·4H2O, respectively, and in all complexes, the symmetry was octahedral.